Interação entre diferentes níveis populacionais iniciais de Pratylenchus brachyurus e cultivares de soja no desenvolvimento da planta e na reprodução do nematóide - Silva, Rafaela Bernardes (2011)
Due to the significant damage that Pratylenchus brachyurus causes to soybean, this study evaluated different initial populations of this nematode and soybean and investigated the effect of this interaction in plant development and nematode reproduction under greenhouse conditions. The experiment was conducted in completely randomized design as a 6x8 factorial, which consisted of six initial nematode populations (0, 50, 75, 100, 250 and 500 eggs, juveniles and/or adults of P. brachyurus) and eight soybean varieties, with seven replicates. The soybean cultivars used were: BRS Valiosa RR; BRSMG 68 [Vencedora]; M 8360 RR; MG/BR 46 (Conquista); BRS Sambaíba; BRS Favorita RR; M-SOY 6101 and BRSMG 750SRR. Nematode inoculum was obtained from infected maize roots. Soybean was sown in 1.5-L plastic pots filled with substrate consisting of sand and soil in 2:1 ratio. Nematode inoculation was done twenty days after sowing, according to the different initial populations. Every day, the plants were watered and, periodically, nutrient solution was added to the substrate. The following characteristics were evaluated 70 days after inoculation: fresh mass of roots and shoots, dried mass of roots and shoots, final nematode population in soil and roots, to determine the reproduction factor. Considering the equilibrium density of the cultivars, BRSMG 68 [Vencedora], BR/MG 46 (Conquista) and M-SOY 6101 behaved as susceptible, allowing the multiplication of the nematode and had low yield. The cultivars BRS Favorita RR and BRSMG 750SRR were tolerant, allowing the multiplication of the nematode and providing high yield. In the intolerant behavior, cultivars M 8360 RR and BRS Sambaíba had lower nematode multiplication with low plant yield. BRS Valiosa RR had some resistance, with relatively high plant yield and hampering nematode multiplication.